EFEKTIVITAS KEBIJAKAN PERDA KABUPATEN BANDUNG NO. 07 TAHUN 2020 TERHADAP PENCAPAIAN DESA WISATA ALAMENDAH - Zakiyah Nur Sholihah; Ayulia Nirwani; Tresna Bela; Fitri Rahmafitria (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
Tourism villages serve as a government strategy to promote equitable development in economic, social, and human resource sectors through the utilization of local potential. The Bandung Regency Government established Regional Regulation No. 07 of 2020 as a legal framework to regulate and guide the sustainable development of tourism villages. This study aims to analyze the effectiveness of the implementation of Regional Regulation No. 07 of 2020 on the achievement of Alamendah Tourism Village as an advanced tourism village in Bandung Regency. The research employs a qualitative approach with policy analysis based on the six evaluation criteria proposed by William N. Dunn, namely effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings indicate that the regulation has been effective in encouraging the development of Alamendah Tourism Village through economic empowerment, cultural preservation, and sustainable environmental management. Furthermore, the success of this policy implementation is supported by strong community participation and collaboration among various stakeholders. Keywords: Tourism Village; Policy Analysis; Community Participation